Physiological responses and stroke-parameter changes during interval swimming in different age-group female swimmer - Tsalis, G.; Toubekis, A. G.; Michailidou, D.; Gourgoulis, V.; Douda, H.; Tokmakidis (The Journal of Strength and Conditioning Research, 2012)
The purpose of the study was to examine the physiological responses, the stroke-parameter changes, and the ability to sustain a velocity corresponding to critical velocity (CV) during interval swimming on female swimmers of different age groups. Eight children (C; age: 10.4 ± 0.6 years), 11 young (Y; age: 13.1 ± 0.4 years), and 7 adults (A; age: 19.9 ± 4.6 years) swam all-out efforts of 50, 100, 200, 400 m for CV and critical stroke rate (CSR) calculation. Subsequently, the swimmers performed an interval training set of 5 × 300-m (C) and 5 × 400-m repetitions (Y and A) at a velocity corresponding to CV. The CV was higher in the Y and A compared with the C group (C: 0.962 ± 0.05, Y: 1.168 ± 0.09, A: 1.217 ± 0.05 m·s-1, p < 0.05). The velocity of 5 × 300 and 5 × 400 m was not different compared with CV (C: 100 ± 2%, Y: 98 ± 3%, A: 98 ± 3% of CV, p > 0.05). The blood lactate concentration was similar between groups and was maintained steady within each group (C: 4.5 ± 1.4, Y: 4.9 ± 1.4, A: 3.9 ± 1.3 mmol/L, p > 0.05). Heart rate was higher in the C and Y compared with the A group during the last 100 m of each repetition (p < 0.05). Stroke rate remained unchanged during the repetitions and was similar between groups and no different to the CSR (p > 0.05). Stroke length of the fifth repetition was 4.5 ± 4.0% shorter compared with the second repetition in the Y and 5.3 ± 2.0% shorter compared with the first repetition in the A group (p < 0.05). During the 28- to 31-minute duration intermittent swimming, children and young and adult female swimmers were able to sustain CV with a steady and similar blood lactate concentration. Decreased stroke length may indicate an earlier fatigue in young and adult swimmers.